When Incivility Is a Form of Civility: Challenging the Comfort of Willful Ignorance. Issue 6 (21st June 2021) - Applebaum, Barbara
Abstract : In this essay, Barbara Applebaum reframes the case for subversive incivility by emphasizing the links between civility, comfort, and willful ignorance. The scholarship defending incivility gives much attention to ascertaining when incivility is justified. While acknowledging the importance of this focus, Applebaum asks whether it fails to adequately acknowledge (1) the role that willful ignorance plays in maintaining systemic privilege and oppression, and (2) how calls for civility are demands for dominant group comfort that protect willful ignorance from challenge. The essay begins with a review of some of the arguments that have been articulated in defense of justified incivility, particularly Tracy Owen Patton's concept of hegemonic civility. Next, Applebaum calls attention to how subversive incivility aims to disrupt the dominant group comfort that preserves willful ignorance, arguing that "incivility" is marked not by the tone of an utterance or argument, but rather by whether the message challenges hegemonic frameworks. She then elaborates the type of ignorance involved in willful ignorance and, finally, uses this concept to analyze a case of student "incivility" at Yale University. Applebaum concludes by recommending a shift in focus from establishing what counts as civility versus incivility to addressing the more fundamental question about what one is unwilling to know.